The internet and friendships of young adults - Paz, Mary Llenell B. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study provides insights to networks and connections of young adults when they are online. It is a descriptive and exploratory research of 18-29 year old Filipinos living, studying or working in Metro Manila on their internet use, Social Networking Site (SNS) activities and friendships. It aims to answer how Social Networking Sites (SNS), if at all, are significant to friendships, and how these sites are used to connect with friends. The study sampled 100 Filipino young adults via random systematic sampling. Invitations were sent by mailing list, email, and Social Networking Site (SNS) messaging. An online survey was used to gather data. Filipino young adults are active users of Social Networking Sites (SNS), most especially the Multi-functional types such as Facebook and Friendster, when connecting with friends. They also view Social Networking Sites (SNS) as a tool that improves friendships. Four types of young adult internet users were also identified in the study. Single students are "Versatile Users", single working respondents are the "Most Connecting", married working respondents are the "Most Connected", and married non-working respondents are "Pastime Users".